Pengaruh Keselamatan Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Internusa Tribuana Citra Multi Finance Cabang Medan - Ronauli Fransiska Pasaribu; Farina Jessen Yap (Pusat Riset dan Inovasi Nasional, 2022)
A finance company is a company that provides loans to prospective borrowers with certain guarantees such as PT. Internusa Tribuana Citra Multi Finance Medan Branch. In this business, company funds are often embedded because of debtors who are in arrears. Therefore, the company has a field officer who functions to collect debtor's house and make a withdrawal of the financing unit that has exceeded the reasonable limit of the time of payment. The implementation of billing activities carried out is definitely related to the work safety of each field officer. Work safety issues such as beatings experienced by field officers have an impact on the implementation of billing. This resulted in the billing process becoming less than optimal because the officers were worried about their safety. In addition, the work environment also impacts on employee performance, such as lack of work space that makes employees not free to work, relationships that are not good affect the communication process in decision making and document filing that is not neat will affect the document search process. The purpose of this study was to determine the effect of work safety and work environment on the performance of employees. The analytical method used is quantitative descriptive analysis method. The population in this study were 51 people who were employees of PT. ITC Multi Finance Medan Branch and also as a respondent. The method of data collection is done by interviewing, distributing questionnaires, documentation and literature. Variables taken with a Likert scale. The data analysis model used to answer the hypothesis is multiple linear regression analysis.The results showed that simultaneously the work safety and work environment did not significantly influence the performance of PT. Medan Branch Internusa Tribuana Citra Multi Finance, and partially has no effect on performance.